2016
DOI: 10.1007/s11092-016-9251-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a data use intervention on educators’ satisfaction and data literacy

Abstract: Schools in many different countries are increasingly expected to use data for school improvement. However, schools struggle with the implementation of data use, because building human capacity around data use in education has not received enough attention. Educators urgently need to develop data literacy skills for being able to use data. For supporting schools with the endeavor of developing data literacy skills, we developed and implemented a data use intervention in secondary schools based in the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 34 publications
2
69
0
5
Order By: Relevance
“…The programme consists of teams who use data collaboratively to solve a selected educational problem within the school. Encouragingly, research results indicated that participation in the intervention led to increased data literacy (Ebbeler et al 2017;Kippers et al 2018). It was reported that several schools were able to solve their problem and improve student achievement (Poortman and Schildkamp 2016).…”
Section: Recommendations For Practicementioning
confidence: 99%
“…The programme consists of teams who use data collaboratively to solve a selected educational problem within the school. Encouragingly, research results indicated that participation in the intervention led to increased data literacy (Ebbeler et al 2017;Kippers et al 2018). It was reported that several schools were able to solve their problem and improve student achievement (Poortman and Schildkamp 2016).…”
Section: Recommendations For Practicementioning
confidence: 99%
“…The data literacy test was based on (1) an already existing knowledge test related to the eight steps of the data use intervention (Ebbeler, Poortman, Schildkamp, & Pieters, 2017), and (2) recent research into data literacy (e.g., Mandinach & Gummer, 2016a), see Appendix A. The data literacy test was constructed by using an extensive protocol on how to construct open-ended test questions, such as adding answer restrictions to the questions (e.g., 'answer in a maximum length of five sentences'), using standard formulations for short-answer questions (e.g., 'identify two data sources' or 'identify two quality criteria of data'), and developing questions with others (e.g., the data literacy test was developed and discussed with researchers who also conduct research into DBDM, the data coach, and a teacher with teaching experience in secondary education) (Erkens, 2011).…”
Section: Data Literacy Testmentioning
confidence: 99%
“…The effective use of data for decision-making and evidence-informed practice is a growing expectation in schools [1], [6] intended to help identify student needs, design targeted school improvements, and implement focused supports and instructional improvement. Arising from this expectation, is the understanding that all educators should possess some degree of data literacy skills that would afford them the capability to understand, interpret, and use data effectively to inform decisions [7], [6].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions include: (1) encouraging collaboration among educators, (2) building common goals/purposes for data use, (3) using multiple data elements or triangulation of data points related to educator's own context, and (4) providing sufficient time or embedding data use in current work contexts [11], [1]. Furthermore, utilizing a model that incorporates elements of direct coaching and responsive support is beneficial and effective in promoting data literacy growth [10], [1]. Educator needs for support for data use are also well documented and include such forms as worksheets, portfolios, and feedback [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation